2021
DOI: 10.3390/ijerph18030973
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Amyotrophic Lateral Sclerosis and Exposure to Particulate Matter from Vehicular Traffic: A Case-Control Study

Abstract: (1) Background: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease with still unknown etiology. Some occupational and environmental risk factors have been suggested, including long-term air pollutant exposure. We carried out a pilot case-control study in order to evaluate ALS risk due to particulate matter with a diameter of ≤10 µm (PM10) as a proxy of vehicular traffic exposure. (2) Methods: We recruited ALS patients and controls referred to the Modena Neurology ALS Care Center bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
(66 reference statements)
2
7
1
Order By: Relevance
“…Similarly, high levels of residential exposure to traffic-derived aromatic solvents has been associated with increased risk of ALS in a U.S. study 36 . However, in a recent case–control we carried out in Italy, we did not find a positive association between PM 10 exposure and ALS, except for a very imprecise increase in risk between 10 and 20 µg/m 3 of annual maximum PM 10 levels 11 . In addition, an interaction between magnetic fields and air pollutants has been proposed due to formation of charged corona ions produced in the vicinity of power lines 37 , 38 .…”
Section: Discussioncontrasting
confidence: 73%
“…Similarly, high levels of residential exposure to traffic-derived aromatic solvents has been associated with increased risk of ALS in a U.S. study 36 . However, in a recent case–control we carried out in Italy, we did not find a positive association between PM 10 exposure and ALS, except for a very imprecise increase in risk between 10 and 20 µg/m 3 of annual maximum PM 10 levels 11 . In addition, an interaction between magnetic fields and air pollutants has been proposed due to formation of charged corona ions produced in the vicinity of power lines 37 , 38 .…”
Section: Discussioncontrasting
confidence: 73%
“…One study involving 917 ALS patients from a Dutch national registry showed an increased risk of ALS in patients with long-term exposure to PM2.5 and NO2, but another series of 52 patients examining PM10 exposure did not replicate these findings. 125,126 Among patients with ALS and Parkinson’s disease, less controversial is the risk of disease aggravation in association with shorter-term exposure to PM2.5, which may lead to first-time admission and diagnosis of the underlying neurological condition. 127…”
Section: Resultsmentioning
confidence: 99%
“…We examined the relation between first and second wave province-specific crude mortality rates from COVID-19 by modeling the mean mortality rate using a restricted cubic spline regression [21], a model that fits a curvilinear pattern to the data as previously reported [22][23][24]. In particular, we fitted a restricted cubic spline model that weighted provincial data by population size, performing both a crude analysis and adjusting for potential confounders.…”
Section: Discussionmentioning
confidence: 99%